2023
DOI: 10.3389/fonc.2023.1204030
|View full text |Cite
|
Sign up to set email alerts
|

The role of EBV-encoded miRNA in EBV-associated gastric cancer

Abstract: Epstein-Barr virus (human herpesvirus 4, EBV) is a linear double-stranded DNA virus that infects over 90% of the population worldwide. However, our understanding of EBV’s contribution to tumorigenesis of EBV-associated GC (EBVaGC) remains incomplete. Recent advancements in EBVaGC research have highlighted that EBV-encoded microRNAs (miRNAs) play prominent roles in critical cellular processes such as migration, cell cycle, apoptosis, cell proliferation, immune response, and autophagy. Notably, the largest group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…In this regard, EBV-miR-BART2-3p may be participating in the inhibition of autophagy. Recent research suggests that the combination of the EBV-BART2-3p with the ULK1 may block the revitalization of the ULK1 from the influence of the AMPK protein [ 54 ]. Changes in the expression of this miRNA could potentially lead to excessive proliferation of immune cells, disrupting the immune system and worsening EBV infections, which may increase the risk of febrile diseases caused by EBV.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, EBV-miR-BART2-3p may be participating in the inhibition of autophagy. Recent research suggests that the combination of the EBV-BART2-3p with the ULK1 may block the revitalization of the ULK1 from the influence of the AMPK protein [ 54 ]. Changes in the expression of this miRNA could potentially lead to excessive proliferation of immune cells, disrupting the immune system and worsening EBV infections, which may increase the risk of febrile diseases caused by EBV.…”
Section: Discussionmentioning
confidence: 99%
“…There is not much discernible distinction to be made that allows specific host–virus interactions to be considered as those promoting tumorigenesis or promoting the demarcation of epigenetic hallmarks observed in EBVaGC, although research with miRNAs has shown modulation of specific cellular processes that eventually contribute to tumorigenesis. For example, EBV miRNAs have confirmed roles in modulating epithelial-to-mesenchymal transition [ 152 ], upregulating E-cadherin expression [ 153 ], binding to cell cycle factors [ 154 ], inhibiting pro-apoptosis proteins [ 155 ], promoting malignant cell transformation [ 155 ], and controlling the movement of killer immune cells into the tumor microenvironment by controlling the senescence-altering sensory phenotypes [ 156 ]. Independent events within these processes and their modulation by EBV miRNAs can promote tumorigenesis, although further research is needed to understand the extent to which EBV interferes in these processes and promotes tumorigenesis.…”
Section: Host Virus Interactions and Epigenetic Hallmarks In Ebv-asso...mentioning
confidence: 99%